Severe Liver Injury Associated With High-Dose Atorvastatin Therapy - Amit Saha MD; Abhimanyu Garg MD (SAGE Publishing, 2021)
Statins are recommended for first-line management of elevated cholesterol in the primary and secondary prevention of atherosclerotic cardiovascular disease. Statins may occasionally be associated with mild transaminase elevations but can also result in life-threatening liver injury. Atorvastatin is the most common cause of clinically significant liver injury in this drug class. We report a case of severe, asymptomatic liver injury in a hepatocellular pattern in a 71-year-old man occurring within 3 months of switching from simvastatin to high-intensity atorvastatin therapy. Hepatitis improved rapidly with cessation of atorvastatin and did not recur after resuming simvastatin.